OPEN BIDDING PHENOMENON JPT PRATAMA POST REGIONAL AUTONOMY - Kamaludin Kamaludin; Rini Indriani (Journal of Business Studies and Management Review, 2019)
The purpose of this study is to capture the phenomenon of the open bidding process carried out in order to select apparatus who have sufficient capacity, competition and integrity to fill certain positions so that they can carry out their tasks more effectively and efficiently. The research design used was a qualitative research design, which investigated the open selection of Echelon III structural officials in the “R” Regency Government Environment (initials in order to maintain the confidentiality of informants) in Bengkulu Province. Research results: (1) The selection of high ranking pratama officials in the Regency District "R" has referred to the laws and regulations; (2) The regional head uses the final result of open bidding in filling the position, based on his authority the regional head does not have to appoint an official who gets the highest score; (3) The inhibiting factor of the open bidding implementation of pratama high-ranking officials in the “R” Regency environment is the fulfillment of competency of the examinees which is not infrequently influenced by the culture of personal closeness and the insistence of politicians to penetrate the structuring of the bureaucratic elite; (4) The perception of the implementation of open bidding related to the determination of each position position, namely selection is a formality impacting on the competence of applicants.